2022
DOI: 10.2196/42839
|View full text |Cite
|
Sign up to set email alerts
|

Economic and Environmental Impact of Digital Health App Video Consultations in Follow-up Care for Patients in Orthopedic and Trauma Surgery in Germany: Randomized Controlled Trial

Abstract: Background Following the Riyadh Declaration, digital health technologies were prioritized in many countries to address the challenges of the COVID-19 pandemic. Digital health apps for telemedicine and video consultations help reduce potential disease spread in routine health care, including follow-up care in orthopedic and trauma surgery. In addition to the satisfaction, efficiency, and safety of telemedicine, its economic and environmental effects are highly relevant to decision makers, particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…From the health provider’s perspective, these results suggest that video consultations might be suitable for use in orthopedic and trauma surgery. The potential of video consultations is further underlined by previous studies that found comparable results to F2F consultations in terms of physician and patient satisfaction, efficiency, quality of care, and benefits from a societal perspective [ 16 , 18 , 19 , 29 - 32 ].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…From the health provider’s perspective, these results suggest that video consultations might be suitable for use in orthopedic and trauma surgery. The potential of video consultations is further underlined by previous studies that found comparable results to F2F consultations in terms of physician and patient satisfaction, efficiency, quality of care, and benefits from a societal perspective [ 16 , 18 , 19 , 29 - 32 ].…”
Section: Discussionmentioning
confidence: 90%
“…In addition, the implementation of telemedicine could result in a competitive advantage for clinics, as communication with patients is simplified and, as a result, a service beyond the local environment could be offered [ 35 ]. As telemedicine is associated with cost and time savings for patients as well, the offering of video consultations could furthermore help to recruit new patients [ 16 , 17 , 19 , 30 ]. The implementation of video consultations could also create the possibility of a home office for physicians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the studies primarily focus on the US and UK; for Europe, there are occasional reports on Spain, 18 Sweden, 19 Portugal, 20 or Germany. 21 In their study on telemedical services in Spain, Morcillo Serra et al, 22 find that the heavy use of telemedicine saved an estimated 6655 net tons of CO 2 eq in 2020. Every telemedical consultation helped save an average of 3.057 kg of net CO 2 eq, and every downloaded medical report instead of getting them to the patients via conventional ways, another 1.5 kg.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the studies primarily focus on the US and UK; for Europe, there are occasional reports on Spain, 18 Sweden, 19 Portugal, 20 or Germany. 21 …”
Section: Introductionmentioning
confidence: 99%